DIGITAL REVITALIZATION OF SILAT MANDAR: A COMMUNITY-ORIENTED EDUCATIONAL APPROACH FOR SAFEGUARDING INTANGIBLE HERITAGE IN TIDUNG ISLAND (Lex localis - Journal of Local Self-Government, 2025)
The Purpose of this study is to create an educational model that is rooted in culture and adaptable to technology, aimed at revitalizing the Silat Mandar tradition within the island communities of Pulau Tidung. This initiative seeks to preserve and convey oral and performative heritage through digital platforms that are engaging, accessible, and pedagogically appropriate. By integrating philosophical values and traditional practices into multimedia educational resources, the project promotes continuity between generations, enhances local identity, and empowers community ownership. Additionally, it acts as a prototype for wider efforts to protect intangible cultural heritage, providing a replicable framework that harmonizes innovation with tradition throughout Indonesia’s various archipelagic regions.The Novelty of this research is found in its combination of ethnographic insight with innovative digital teaching methods to rejuvenate the Silat Mandar tradition within a culturally diverse island environment. Unlike earlier initiatives that concentrated exclusively on documentation or performance-based tourism, this study presents a community-centered, multimedia instructional model  that reinterprets oral and practical heritage into organized, mobile-friendly learning materials. By incorporating philosophical values and practices like palang pintu into a pedagogically robust framework, such as ADDIE, this effort bridges generational divides and repositions Silat Mandar as both a cultural treasure and a vibrant educational experience. The application of mixed-methods evaluation to assess emotional engagement, identity development, and intergenerational effects further sets this model apart as a living archive  rather than merely a curriculum. Additionally, its potential for scalability and adaptability in other island communities represents a significant step forward in the digital conservation of intangible heritage, providing a replicable model for culturally aware education in Indonesia’s archipelagic setting.Conclusion of this study indicates that the digital revitalization of Silat Mandar in Pulau Tidung can effectively protect and convey cultural heritage when informed by ethnographic understanding, well-organized instructional design, and community involvement. By incorporating philosophical and performative aspects into multimedia educational resources, and situating the process within a context-sensitive, iterative research and development framework, the project encourages engagement across generations, fosters a sense of cultural ownership, and maintains pedagogical significance. This resulting model not only improves access to education rooted in tradition but also acts as a replicable framework for preserving intangible heritage throughout Indonesia’s island communities.